VD_FINDINFO HC / 2010 / 485 vom 16. September 2010 - VD Tribunal cantonal (2010)
EXPULSION DE LOCATAIRE, DEMEURE DU DÉBITEUR, POUVOIR D'EXAMEN LIMITÉ, CONDITION DE RECEVABILITÉ | 257d al. 2 CO, 257d CO, 25 LPEBL